1989
DOI: 10.2752/089279390787057829
|View full text |Cite
|
Sign up to set email alerts
|

Pet Ownership and Attachment as Supportive Factors in the Health of the Elderly

Abstract: In order to examine pet ownership and pet attachment as factors supporting the health of the elderly, a national probability sample of Americans 65 years of age and older was drawn. Participants answered telephone survey questions regarding pet ownership, life stress, social support, depression, and recent illness. In multiple regression analyses, pet ownership failed to predict depression and illness behavior, while pet attachment significantly predicted depression but not illness experience. In a group with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
209
3
15

Year Published

1990
1990
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 342 publications
(232 citation statements)
references
References 31 publications
5
209
3
15
Order By: Relevance
“…Two studies of the elderly found that greater attachment to one's pet was associated with better mental health (Garrity et al, 1989;Ory & Goldberg, 1983), and attachment was associated with better physical health when human companionship was inadequate (Garrity et al, 1989). Moreover, a survey of elderly persons yielded reports of greater pet involvement if the pet was a dog than a cat (Lago, Knight, & Connell, 1983).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two studies of the elderly found that greater attachment to one's pet was associated with better mental health (Garrity et al, 1989;Ory & Goldberg, 1983), and attachment was associated with better physical health when human companionship was inadequate (Garrity et al, 1989). Moreover, a survey of elderly persons yielded reports of greater pet involvement if the pet was a dog than a cat (Lago, Knight, & Connell, 1983).…”
Section: Discussionmentioning
confidence: 99%
“…Several epidemiologic studies (Comstock & Helsing, 1976;Frerichs, Aneshensel, & Clark, 1981 ;Husaini, Neff, Harrington, Hughes, & Stone, 1980) found the scale sensitive to differences in level of depressed mood. The CES-D has adequate validity (content, criterion-based, and construc0 and reliability (test-retest and internal consistency; Radloff, 1977;Weissman, Shoiomskas, Pottenger, Prusoff, & Locke, 1977) and has been used previously with aged populations (Berkman et al, 1986;Garrity et al, 1989;Murrell, Himmelfarb, & Wright, 1983).…”
Section: Methodsmentioning
confidence: 99%
“…This last issue is particularly important given that immigrant older people are at greater risk of experiencing social isolation, loneliness and reduced social participation (Stephens, Alpass, Towers, & Stevenson, 2011;de Jong Gierveld, Van Tilbur, & Dykstra, 2006) and that those who are more socially integrated tend to live longer (Antonucci et al, 2014). Accordingly, there is evidence to suggest that pet ownership can directly enhance health and wellbeing or indirectly act as a buffer against stressful events, particularly for older people (Garrity, Stallones, Marx & Johnson, 1989;Winefield, Black, & Chur-Hansen, 2008). …”
Section: Working Towards Ageing Well In and Around Rosewood Towersmentioning
confidence: 99%
“…Empirical research of HAI, including studies of pet ownership and animal-assisted therapy, suggests potential human outcomes may include improvements in psychiatric symptomatology, psychological states, and social behavior (e.g., Garrity, Stallones, Marx, & Johnson, 1987;Hecht, McMillan, & Silverman, 2001). Studies researching these psychosocial effects of HAI are particularly common in institutional settings such as inpatient psychiatric hospitals and nursing homes (Johnson, Odendaal, & Meadows, 2002).…”
mentioning
confidence: 99%